The view from Saturday - Konigsburg, E. L. (Atheneum Books for Young Readers, 1996)
Four students, with their own individual stories, develop a special bond and attract the attention of their teacher, a paraplegic, who choses them to represent their sixth-grade class in the Academic Bowl competition.